Tubgcp3 Is Required for Retinal Progenitor Cell Proliferation During Zebrafish Development - Li, Guobao; Jin, Daqing; Zhong, Tao P. (Frontiers in Molecular Neuroscience, 2019)
The centrosomal protein γ-tubulin complex protein 3 (Tubgcp3/GCP3) is required for the assembly of γ-tubulin small complexes (γ-TuSCs) and γ-tubulin ring complexes (γ-TuRCs), which play critical roles in mitotic spindle formation during mitosis. However, its function in vertebrate embryonic development is unknown. Here, we generated the zebrafish tubgcp3 mutants using the CRISPR/Cas9 system and found that the tubgcp3 mutants exhibited the small eye phenotype. Tubgcp3 is required for the cell cycle progression of retinal progenitor cells (RPCs) and its depletion caused cell cycle arrest in mitotic (M) phase. The M-phase arrested RPCs exhibited aberrant monopolar spindles and abnormal distributed centrioles and γ-tubulin. Moreover, these RPCs underwent apoptosis finally. Our study provides the in vivo model for the functional study of Tubgcp3 and shed lights on the roles of centrosomal γ-tubulin complexes in vertebrate development.